IMPLEMENTASI LAYANAN HOME VISIT DALAM PENGUMPULAN DATA INFORMASI SISWA BIMBINGAN DAN KONSELING - Stevandy, Matias; Pangestie, Esty Pan; Feronika, Nopi (Universitas Palangka Raya, 2023)
This study aims to determine the implementation of home visit services in collecting information on guidance and counseling students at junior high school 8 Palangka Raya. The research method used is qualitative methods, where in qualitative research the main instrument is the researcher himself. In this study, the collection techniques used were interviews, observation, and documentation. This research was conducted at junior high school 8 Palangka Raya, March 2022 – June 2022. In this study using data analysis techniques Miles and Humberman. The results of this study indicate that the application of home visit services in collecting student information data at junior high school 8 Palangka Raya has been going well where Guidance and Counseling teachers not only solve student problems through home visits but Guidance and counseling teachers also assist the school in updating information students when providing home visit services to be able to help the school update students' personal data at school.